Examining Foreign Language Anxiety’s Impact on English Education Students’ Speaking Skills at Universitas Muhammadiyah Riau - A Ardiya; Bumi, Serai Wangi; N Nurfaisal (Journal of Science and Education (JSE), 2025)
Anxiety is widely recognized for its significant impact on language learners' performance, commonly known as Foreign Language Anxiety (FLA) in language learning contexts. A major source of this anxiety is the fear of negative evaluation. This study aimed to investigate how English education students at Universitas Muhammadiyah Riau perceive the fear of negative evaluation in relation to their speaking ability. Using a qualitative approach with a descriptive research method, the study employed convenience sampling to select participants from the English education program. Data collection involved distributing questionnaires and conducting interviews to gain deeper insights into students' perspectives. The findings indicate that a substantial proportion of students (63.2%) reported experiencing fear of negative evaluation during their speaking classes. The primary concern identified among participants was the fear of making mistakes in front of both lecturers and peers, with an overwhelming majority (94.7%) expressing agreement on this issue. This study sheds light on the specific anxieties faced by English education students in a university context, underscoring the pervasive impact of fear of negative evaluation on their language learning experiences. By exploring these perceptions, the study contributes valuable insights into understanding the psychological barriers that hinder students' speaking abilities in the English language classroom. Addressing these anxieties is crucial for developing effective strategies to support students in overcoming their fear and enhancing their language proficiency and confidence